PROMOTION, INFLUENCER MARKETING, AND ONLINE CUSTOMER REVIEW ON PURCHASE DECISIONS IN SHOPEE E-COMMERCE (A CASE STUDY ON THE COMMUNITY IN PEKANBARU) - Achmad Tavip Junaedi; Nabila Hestia; Suhardjo Suhardjo; Jenny Angelica; Nicholas Renaldo; Amries Rusli Tanjung; Novita Yulia Putri; Marice Br Hutahuruk; Yusnidar Yusnidar; Muhammad Adrian Agusta (Procuratio : Jurnal Ilmiah Manajemen, 2025)
This research investigates the influence of Promotion, Influencer Marketing, and Online Customer Reviews on purchase decisions in the E-Commerce platform Shopee in Pekanbaru. The determination of the research sample utilizes accidental sampling. This study employs primary data, which is directly obtained from respondents by distributing questionnaires or statement lists to the predetermined sample. Secondary data generally consists of evidence, records, or historical reports organized in published archives. The method used is multiple linear regression analysis with a sample size of 100 respondents. The research findings indicate that Promotion and Online Customer Review significantly influence purchase decisions on Shopee E-commerce in the city of Pekanbaru, while Influencer Marketing does not significantly affect purchase decisions on Shopee E-commerce in the city of Pekanbaru. Penelitian ini bertujuan untuk mengetahui pengaruh Promosi, Influencer Marketing, dan Online Customer Review terhadap keputusan pembelian pada platform E-Commerce Shopee di Pekanbaru. Penentuan sampel penelitian menggunakan teknik accidental sampling. Penelitian ini menggunakan data primer yang diperoleh langsung dari responden dengan cara menyebarkan kuesioner atau daftar pernyataan kepada sampel yang telah ditentukan. Data sekunder pada umumnya berupa bukti-bukti, catatan, atau laporan historis yang terorganisasi dalam arsip yang diterbitkan. Metode yang digunakan adalah analisis regresi linier berganda dengan jumlah sampel sebanyak 100 responden. Hasil penelitian menunjukkan bahwa Promosi dan Online Customer Review berpengaruh signifikan terhadap keputusan pembelian pada E-Commerce Shopee di Kota Pekanbaru, sedangkan Influencer Marketing tidak berpengaruh signifikan terhadap keputusan pembelian pada E-Commerce Shopee di Kota Pekanbaru.